Molecular basis of hereditary C3 deficiency. - Botto, M (1990)
Hereditary deficiency of complement component C3 in a 10-yr-old boy was studied. C3 could not be detected by RIA of serum from the patient. Segregation of C3 S and C3 F allotypes within the family confirmed the presence of a null gene for C3, for which the patient was homozygous. 30 exons have been characterized, spanning the entire beta chain of C3 and the alpha chain as far as the C3d region. Sequence analysis of the exons derived from the C3 null gene showed no abnormalities in the coding sequences. A GT-AT mutation at the 5' donor splice site of the intervening sequence 18 was found in the C3 null gene. Exons 17-21 were amplified by the polymerase chain reaction (PCR) from first-strand cDNA synthesized from mRNA obtained from peripheral blood monocytes stimulated with LPS. This revealed a 61-bp deletion in exon 18, resulting from splicing of a cryptic 5' donor splice site in exon 18 with the normal 3' splice site in exon 19. This deletion leads to a disturbance of the reading frame of the mRNA with a stop codon 17 bp downstream from the abnormal splice in exon 18. His parents had both the normal and abnormal C3 mRNA and were shown to be heterozygous for this mutation by sequence analysis of genomic DNA amplified by PCR. Similar splice mutants have previously been reported in the beta-globin, phenylalanine hydroxylase, and porphobilinogen deaminase genes. This mutation is sufficient to cause the deficiency of C3 in the patient.